全球公民素養的學習成效之探究－以連結至社區機構實作為途徑 - 陳淑敏(Shu-Min Chen) (Jiao ke shu yan jiu, 2024)
Globalization has a major effect on the world, necessitating the enhancement of global citizenship among university students. This paper examines the teaching practices involved in the Globalization and Citizenship course in university settings. It outlines the rationale for program planning from epistemological and pedagogical perspectives. This course enables students to participate in community organizations, thereby enhancing their understanding of globalization in real life. In this study, the author used an action research method and multiple data collection techniques to explore the experiences and performance of college students in acquiring global citizenship, including their experiences in connecting with community organizations. The research findings are as follows. First, in terms of learners’ performance, the foundational subject knowledge provided by the general curriculum is crucial for ensuring successful learning outcomes. Second, in terms of deepening the epistemology of global citizenship c